The Kaposi’s Sarcoma-Associated Herpesvirus ORF57 Protein and Its Multiple Roles in mRNA Biogenesis - Jackson, Brian R.; Noerenberg, Marko; Whitehouse, Adrian (Frontiers in Microbiology, 2012)
Post-transcriptional events which regulate mRNA biogenesis are fundamental to the control of gene expression. A nascent mRNA is therefore steered through multimeric RNA-protein complexes that mediate its capping, splicing, polyadenylation, nuclear export and ultimately its translation. Kaposi’s sarcoma-associated herpesvirus (KSHV) ORF57 is a functionally conserved protein found in all herpesviruses which plays a pivotal role in enhancing viral gene expression at a post-transcriptional level. As such, ORF57 has been implicated in multiple steps of RNA biogenesis, including augmenting viral splicing, protecting viral RNAs from degradation to enhancing viral mRNA nuclear export and translation. In this review, we highlight the multiple roles of KSHV ORF57 in regulating the post-transcriptional events which are fundamental to the control of virus gene expression.